1982
DOI: 10.1002/jctb.5030320306
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the crystallisation of gallium hydroxide precipitated from hydrochloric acid solutions by various alkalis

Abstract: Gallium hydroxide precipitated from aqueous gallium chloride solution on addition of alkalis at varying pH have been aged in the mother liquors for different periods of time. The resulting precipitates have been examined by X‐ray diffraction and i.r. spectrophotometry. It is found that the precipitate, separated immediately from the mother liquor after preparation, exists in an amorphous type and transforms to α‐gallium oxyhydroxide during aging independent of pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 4 publications
4
23
1
Order By: Relevance
“…A broad H-O-H stretching vibration band is at about 2938 cm -1 and O-H streching of GaOOH is at about 2832 cm -1 . 14 The bands at 2036 and 1942 cm -1 , together with those at 1038 and 960 cm -1 were assigned to constitutional Ga-OH bending modes and their overtones respectively, in close agreement with those reported by Sato et al 15 The IR band at 688 cm -1 could be assigned to ν(OH) Figure 5 Photoluminescence spectrum of GaOOH nano-platelets with excitation wavelength at 200 nm. deformation vibration, whereas the groups of bands (including those at 640 and 486 cm -1 ) were assigned to Ga 2 O bending modes.…”
Section: Resultssupporting
confidence: 80%
“…A broad H-O-H stretching vibration band is at about 2938 cm -1 and O-H streching of GaOOH is at about 2832 cm -1 . 14 The bands at 2036 and 1942 cm -1 , together with those at 1038 and 960 cm -1 were assigned to constitutional Ga-OH bending modes and their overtones respectively, in close agreement with those reported by Sato et al 15 The IR band at 688 cm -1 could be assigned to ν(OH) Figure 5 Photoluminescence spectrum of GaOOH nano-platelets with excitation wavelength at 200 nm. deformation vibration, whereas the groups of bands (including those at 640 and 486 cm -1 ) were assigned to Ga 2 O bending modes.…”
Section: Resultssupporting
confidence: 80%
“…In the presence of alkali, the α -GaOOH nanoparticles precipitated immediately due to the reaction between the hydrated gallium as Ga(OH) 3 and ammonium hydroxide in the supersaturated condition [33,34]. The unstable nanoparticles were subsequently aggregated by the well-known van der Waals force to form bigger nanoparticles [35].…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that water molecules remained in the precipitated α -GaOOH nanorods [44]. Other than the water molecule-related peaks, the strong bending vibrations at 1019 and 945 cm −1 were attributed to the Ga–OH bands in the α -GaOOH nanorods [26,34]. The strong bands at 649 cm −1 and 477 cm −1 represented the Ga–O bending vibration and Ga–O stretching vibration [45], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recommended that the amorphous precipitate was isolated immediately after preparation; otherwise, it converted into α-GaOOH with ageing in the original liquid, independently of pH. [14] α-GaOOH was also obtained after reacting GaCl 3 and tetraammonium hydroxide in pH 3-10 at 60°C for 1-7 days, [15] or by sonochemical hydrolysis of the starting material in distilled water for 6 h at room temperature. [16] Calcination of α-GaOOH at >500°C gave α/β-Ga 2 O 3 products.…”
Section: Introductionmentioning
confidence: 99%